A Case Study of Pursued Lip Breathing to Prevent Asthma Relaps - Cahyadi Kurniawan, Ikna; Setiawan, Henri (Alta Dharma Publisher, 2022)
Introduction: Asthma is a disease that affects the human respiratory system, so this disease can be categorized as a group of immune diseases that attack the respiratory system. One of the non-pharmacological therapies for asthma can be done with pursued lip breathing (PLB) exercise. Objective: This case study was conducted to describe the pursed lip breathing intervention in reducing shortness of breath in asthmatic clients. Method: This study used a case study design with an evidence based practice implementation approach that focuses on nursing interventions. The research was conducted at the BLUD of Banjar City General Hospital on 27-31 May 2022. The participants in this study was Mrs. S, 65 years old, female, main problem with shortness of breath. The process of assessing and establishing a diagnosis is focused on the main problem. Objective and subjective data becomes a reference for periodic evaluation of nursing implementation. Result: According to the client's admission, asthma usually recurs every 1-2 weeks because of strenuous and tiring activities. However, when confirmed on June 20, 2022, the client admitted that he had not relapsed. Conclusion: The pursed lip breathing intervention is supposed to be effective in reducing shortness of breath in asthmatic clients as evidenced by the client's subjective acknowledgment, although it has not been supported by normal breathing frequency as an indicator of physical health. Theoretically, this research does not conflict with previous research so that it can be a reference in future research. Clinically, pursed lip breathing intervention can be an alternative intervention to reduce shortness of breath in clients with chronic diseases such as asthma in hospitals and health centers. Keywords: asthma, dypsnea, pursued lip breathing